Development needs of pastoral and agropastoral production systems in Ethiopia: Lessons learnt from ILRI's research in some pastoral areas of Ethiopia - Berhe, Kahsay; Gebremedhin, Berhanu; Ehui, Simeon K.; Mohamed-Saleem, M.A. (Mekelle University, 1999)
Lowlands in Ethiopia cover about 60 percent of the total land area, of which about 60 percent is arid. Land use in the lowlands is dominated by pastoralist and agropastoralist production systems. Livestock production constitutes the most important component of the system and rangeland is the major source of feed. Lowland breeds of livestock play an important role in the national economy of Ethiopia. For example, by the mid 1980s, 90 percent of the total export of live animals was comprised of lowland breeds of cattle and sheep. Lowland cattle also contributed about 20 percent of the draft animals in the highlands. The International Livestock Research Institute (ILRI), and its predecessor, the ILCA has conducted research on pastoral and agropastoral production systems in Ethiopia for more than a decade. These studies focused on the Borana plateau of southern Ethiopia, the Jijiga area in eastern Ethiopia and other places. This paper draws on studies carried out by ILRI and presents results on vegetative dynamics and resource use, livestock management, socio-economic contributions and constraints, and policy issues related to the Development of pastoral systems. Appropriate attention to the pastoral and agropastoral systems should remain an important focus of future agricultural Development strategies.